2020
DOI: 10.21203/rs.3.rs-87766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Balloon Occluded TACE (B-TACE) vs DEM-TACE for HCC. A Single Center Retrospective Case Control Study.

Abstract: Background To compare oncological results and safety profile of balloon micro-catheter trans-arterial chemoembolization (b-TACE) and drug-eluting-microsphere (DEM-TACE) in patients with hepatocellular-carcinoma (HCC).Methods This is a case-control, retrospective, single-center study. Between January-2015/March-2019, 149 patients (131 males [87.9%]) with 226 HCC were treated, 22 patients (35 HCC; 19 [86.4%] males) with b-TACE and 127 with DEM-TACE (191 HCC, 112 [88.2%] males). Embolization protocol was standard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Lucatelli et al and Golfieri et al reported that B-TACE achieved the best clinical performance for 3-5 cm of nodular size in treatment. [35,36] It is still unclear why B-TACE is more effective in cases with a bigger tumor size. However, a report showed the relationship between an increase in microvascular invasion or microsatellite lesions and bigger tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Lucatelli et al and Golfieri et al reported that B-TACE achieved the best clinical performance for 3-5 cm of nodular size in treatment. [35,36] It is still unclear why B-TACE is more effective in cases with a bigger tumor size. However, a report showed the relationship between an increase in microvascular invasion or microsatellite lesions and bigger tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…[26] In contrast, HIFU has the effect of regulating immunity and inhibiting viral replication, and has better efficacy in treating HB in children, and it is easy to take and has few adverse effects, which provides a new way and method for the treatment of chronic hepatitis. [27] Although this study is novel but also has shortcomings, HIFU has been widely recognized for the treatment of HB in children, but as an emerging treatment modality, there are still many basic theories, such as ultrasound dosimetry, thermal dosimetry, noninvasive temperature monitoring, and moderate modulation of cavitation effects, that need to be studied in depth. Meanwhile, the role and status of HIFU in the treatment of HB in children also needs to be confirmed by more data from large sample, multicenter prospective clinical randomized controlled studies.…”
Section: Tang Et Al • Medicine (2022)mentioning
confidence: 99%
“…The first case-control study comparing B-DEM-TACE vs. DEM-TACE came from the Italian team of Lucatelli et al [93]. The objective response was similar between the two techniques at 1 and 3 months but was favorable for B-DEM-TACE at 9-12 months (78.9% vs. 53.9%, p = 0.05).…”
Section: More Precise With New Cathetersmentioning
confidence: 99%